Salience of Law Enforcement: A Field Experiment - Robert Dur; Ben Vollaard (Institute of Labor Economics (IZA), 2018)
We conduct a field experiment to examine whether the deterrent effect of law enforcement depends on the salience of law enforcement activity. Our focus is on illegal disposal of household garbage in residential areas. At a random subset of 56 locations in a mid-sized city, law enforcement officers supplemented their regular enforcement activities by the practice of putting brightly-colored warning labels on illegally disposed garbage bags. This treatment made the existing enforcement activities suddenly much more apparent to residents. We find evidence for a substantial reduction in illegal disposal of garbage in response to the treatment.
Keywords: C93; K42; 330; law enforcement; deterrence; perception; salience; disorder